Concept and performance testing of an all-steel miniature dual stiffness damper. (August 2021) - Wang, Weiyang; Liu, Ye
Abstract: The double-stage yield buckling-restrained braces gradually play a role in different floors, so as to control the structural deformation pattern and hinder the weak-story collapsing. In this study, a novel all-steel damper called the miniature dual stiffness damper (MDSD) was proposed, which had the advantages of simple assembly and low cost. A series of tests was performed under quasi-static test to address the hysteretic behavior of MDSDs with different stiffness ratios of the large yield segment to the small yield segment, K yl /K ys . The test results demonstrated that MDSDs had a stable hysteretic behavior, and the dual stiffness can be achieved by yielding successively in small and large yield segments. The second stiffness of the MDSD increased with the increase of K yl /K ys when the elastic stiffness of the small yield segment kept unchanged. The low-cycle fatigue life of the MDSD was negatively correlated with the strain of the small yield segment. An in-series stiffness model for the MDSD was presented. The theoretical hysteretic curves of MDSDs were further obtained based on the proposed stiffness model, and a good accuracy was achieved. Graphical abstract: Unlabelled Image Highlights: A novel all-steel miniature dual stiffness damper (MDSD) is proposed. The small and large yield segments of the MDSD enter plastic successively, forming the dual stiffness characteristic. An in-series stiffness model and the derivation of theoretical hysteretic curves are proposed.